Coadministration of cruzipain and GM-CSF DNAs, a new immunotherapeutic vaccine against Trypanosoma cruzi infection - Cerny, Natacha (2015)
Therapeutic vaccine research and development are especially important in Chagas disease considering the characteristics of the chronic infection and the number of people in the Americas living with a parasite infection for decades. We have previously reported the efficacy of attenuated Salmonella enterica (S) carrying plasmid encoding cruzipain (SCz) to protect against Trypanosoma cruzi infection. In the present work we investigated whether Cz DNA vaccine immunotherapy could be effective in controlling an ongoing T. cruzi infection in mice. We here report the intramuscular administration of naked Cz DNA or the oral administration of Salmonella as Cz DNA delivery system as therapeutic vaccines in mice during acute or chronic infection. The coadministration of a plasmid encoding GM-CSF improved vaccine performance, indicating that the stimulation of innate immune cells is needed in the event of an ongoing infection. These therapeutic vaccines were able to address the response to a protective and sustained Th1 biased profile not only against Cz but also against a variety of parasite antigens. The combined therapeutic vaccine during the chronic phase of infection prevents tissue pathology as shown by a reduced level of enzyme activity characteristic of tissue damage and a tissue status compatible with normal tissue. The obtained results suggest that immunotherapy with Cz and GM-CSF DNAs, either alone or in combination with other drug treatments, may represent a promising alternative for Chagas disease therapy.